Kajian Yohanes 8:1-11 Sebagai Dasar Pelayanan Pendampingan Terhadap Orang Kristen Yang Berzina di Jakarta - Pardede, Harold (Sekolah Tinggi Teologi Adhi Wacana Surabaya, 2024)
Adultery is an offense or activity that is commonplace in large and metropolitan cities such as Jakarta. Perpetrators of adultery will usually receive legal and social sanctions from the surrounding community. The same thing happened to the woman who was caught in adultery in the text John 8:1-11. The woman was judged unfairly according to the law by the scribes and Pharisees. In contrast to the scribes, Jesus was there to provide forgiveness and assistance to the woman who committed adultery. Through this research, the author wants to provide the example and method that Jesus gave as a guide to how to deal with cases of adultery which are rampant among Christians in Jakarta. This research uses the hermeneutic method and literature study of the story of the woman who committed adultery in the text John 8:1-11. Through this research, it is hoped that Christians, especially God's servants, will be able to emulate the attitude of Jesus who forgave and accompanied every Christian in Jakarta who fell into the sin of adultery.